ANALISIS PERJANJIAN CLOUD TERHADAP POTENSI PERANG SIBER DARI PERSPEKTIF ASAS KEPENTINGAN MILITER - Alessandro Praputranto; Jun Justinar (Fakultas Hukum Universitas Trisakti, 2022)
The agreement program between the countries dubbed the cloud act was followed by the UnitedStates of America along with Northern Ireland and the United Kingdom. This agreement regulatesthe obligations of member countries of this multilateral agreement to comply with theirobligations to store, back up, or disclose their electronic data regardless of where the informationis located. From here it can be seen that there will be a